2019
DOI: 10.1097/dss.0000000000001964
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of a 35% Glycolic Acid Peel Alone or in Combination With a 10% and 20% Trichloroacetic Acid Spot Peel for Melasma: A Randomized Control Trial

Abstract: BACKGROUND To study and compare the therapeutic efficacy and side effects of a 35% glycolic acid (GA) full face peel alone or in combination with a 10% or 20% trichloroacetic acid (TCA) spot peel for facial melasma. METHODS Thirty patients with facial melasma were randomly divided into 3 equal Groups A, B, and C. Group A was treated with a 35% GA full-face peel, Group B and C with 35% GA full-face peel followed by a 10% and 20% TCA spot peel respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…They reasoned that because of some inherent factors in this group (combined GA & TCA), for example the use of oral contraceptives. 11…”
Section: Discussionmentioning
confidence: 99%
“…They reasoned that because of some inherent factors in this group (combined GA & TCA), for example the use of oral contraceptives. 11…”
Section: Discussionmentioning
confidence: 99%
“…Incluyó Los peelings superficiales con AG, AS y TCA deberían considerarse tratamientos de segunda línea. Los peelings con AG al 35% pueden ser útiles en el tratamiento del melasma [28]; Sarkar et al [29] mostraron que los peelings de AG 35% y salicílico-mandélico 20% pueden mejorar el melasma en pieles oscuras, y Dayal et al [30] alcanzaron resultados prometedores combinando AG (30-50%) y AA. Las exfoliaciones con TCA combinadas con solución de Jessner podrían ser una alternativa prometedora en el tratamiento del melasma recalcitrante, pero se necesitan estudios de mayor tamaño muestral [31].…”
Section: Discussionunclassified
“…16 Another more recent study using chemical peels with TCA alone or combined with glycolic acid showed a significant improvement in melasma in both. 17 Daily treatment with mild depigmenting agents has been shown to help maintain the treatment effects of peeling. 18 It is important in this population to use a broadspectrum sunscreen with high SPF and good protection against UVA and visible light, which are known aggravating factors of pigmented lesions and melasma.…”
Section: Discussionmentioning
confidence: 99%